2011
DOI: 10.1210/jc.2010-2381
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Four Different Tyrosine Kinase Inhibitors on Medullary and Papillary Thyroid Cancer Cells

Abstract: There is indeed specificity for different RET mutations, with XL184 being the most potent inhibitor in MEN2A and PTC and vandetanib the most effective in MEN2B in vitro. No TK inhibitor was superior for all the cell lines tested, indicating that mutation-specific therapies could be beneficial in treating MTC and PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 22 publications
5
48
0
Order By: Relevance
“…Cabozantinib is a potent inhibitor of RET kinase activity and the proliferation of TT cells in vitro. Our results for inhibition of TT cell proliferation are concordant with those of a previous study, which also showed that cabozantinib is a significantly more potent inhibitor of TT cell proliferation than vandetanib, sunitinib, or axitinib (50). In vivo pharmacodynamic studies showed substantial inhibition of RET in TT xenograft tumors following a single oral dose of cabozantinib.…”
Section: Cabozantinib Inhibits Tt Tumor Growthsupporting
confidence: 91%
See 4 more Smart Citations
“…Cabozantinib is a potent inhibitor of RET kinase activity and the proliferation of TT cells in vitro. Our results for inhibition of TT cell proliferation are concordant with those of a previous study, which also showed that cabozantinib is a significantly more potent inhibitor of TT cell proliferation than vandetanib, sunitinib, or axitinib (50). In vivo pharmacodynamic studies showed substantial inhibition of RET in TT xenograft tumors following a single oral dose of cabozantinib.…”
Section: Cabozantinib Inhibits Tt Tumor Growthsupporting
confidence: 91%
“…Given the evidence for co-expression of MET and RET in MTC tumor tissue, we characterized the ability of cabozantinib to inhibit the kinase activity of three mutated RET variants found in MTC patients. In biochemical assays, cabozantinib inhibited the RETactivating kinase domain mutation M918T with an IC 50 of 27 nmol/L, and to a lesser extent the Y791F mutant (IC 50 1173 nmol/L). Cabozantinib was not active against the RET mutant V804L (IC 50 > 5000 nmol/L) previously shown to render resistance to other RET inhibitors (43).…”
Section: Cabozantinib Is a Potent Inhibitor Of Ret In Vitromentioning
confidence: 98%
See 3 more Smart Citations